Identity of Nyctimystes cheesmani (Anura: Hylidae), with description of two new related species - Kraus, Fred (Zootaxa, 2012)
Using morphological and call data, I redescribe the taxonomically problematic Papuan hylid frog Nyctimystes cheesmanibased on specimens collected at similar elevation to and within 5 km of the type locality. It has long been known thatseveral species of Nyctimystes closely related to N. cheesmani remain to be described in New Guinea, but diagnosis anddescription of these species has languished for decades in the absence of a clear exposition of what constitutes true N.cheesmani. This species is characterized by having vocal slits; a small heel tubercle; basal webbing on hand; exposedtympanum; vertical lines of palpebral reticulum oriented obliquely and with relatively few horizontal cross-connections;pale-tan iris; rear of thighs barred/mottled with brown, caramel, or blue-gray; and call a single, quiet pulsed croak deliv-ered relatively slowly in long trains and with a dominant frequency around 1.9 kHz. It is currently known only from theimmediate vicinity of the type locality, and its exact distribution throughout the Owen Stanley Mts. remains to be deter-mined. I also describe two new species related to N. cheesmani from Milne Bay Province, Papua New Guinea. Both aresimilar to N. cheesmani in morphometric measurements but are easily distinguished from that species by their advertise-ment calls and by details in color pattern. The first species is known only from the southernmost extent of the Owen Stanley Mts and the adjacent Cloudy Mts., the second is endemic to the D’Entrecasteaux Archipelago.